Pelatihan Bahasa Inggris dalam Meningkatkan Keterampilan Berbicara Siswa SD di Kawasan Wisata Kabila Bone - Umar, Irmawaty (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Mastery of English speaking skills is an essential need for communities living in tourism villages, including Kabila Bone Tourism Village. This ability is crucial for communicating with visitors, especially international tourists, in order to introduce and promote local products. However, the local community, including elementary school students, still faces limitations in English speaking skills.To address this issue, this community service program aims to develop tourism-based English speaking skills among elementary school students in Kabila Bone Tourism Village. The training was conducted at SD Negeri 2 Kabila Bone, involving 20 students as participants. The methods applied included lectures, question-and-answer sessions, and role play activities. Lectures were used to provide basic understanding, while question-and-answer and role play were designed to practice communication skills in real contexts.This program is expected to improve students’ English speaking skills and strengthen their knowledge and communication abilities relevant to the local tourism context. As a result, students will be better prepared to interact with tourists visiting Kabila Bone Tourism Village.